Education and Politics in the Age of Uncertainty: A Phenomenological Glance - Vanna Iori (University of Bologna, 2020)
The phenomenological glance combines the capacity to «see» with the responsibility to act accordingly. From this encounter between theoretical and ethical rigour derives the political commitment. In this article the phenomenological foundations of political acting are outlined and the most urgent educational problems of our society are discussed. The renewal of the educational system in relation to the new knowledge, the investment on human rights and cultural opportunities in the face of an increasing educational poverty, the regulation of the web and its defence against its own degenerations, are as many pedagogical and political challenges, that we must address, if we don't want democracy to surrender to disorder and violence.